Democracy and disrespect. (December 2019) - Müller, Jan-Werner
The essay takes the widespread complaint that societies today are deeply divided and polarized as a starting point. Affirming that there is no democracy without division, it asks what it means for conflict and disagreement to be dealt with in a respectful and civil manner. As an illustration of the main argument, the way that liberals (in the broadest sense) have engaged with populist leaders is criticized on both a strategic and normative level. An alternative to existing strategies of dealing with the conflict between liberals and populist is then proposed. Finally, the article also asks under what conditions civil disobedience might be an appropriate response to authoritarian populism.